Effectiveness of Filtration Systems Based on Silica Sand, Bagasse, And Activated Carbon With Varying Media Thicknesses on the Reduction of Ph, Cod, Tss, And Phosphate in Laundry Wastewater - Pramesya Ramadhana Arifin; Yuvita Dian Siswanti; Rusdiana Setyaningtyas; Latifa Mirzatika Al-rosyid; Winda Islamiyah Umarie (PT. Keberlanjutan Strategis Indonesia, 2026)
The growth of laundry businesses has led to an increase in the volume of wastewater containing detergents, organic matter, suspended solids, and phosphates, posing a potential environmental pollution risk if discharged without treatment. This study aimed to analyze the effects of varying the thickness of filtration media—composed of silica sand, bagasse, and activated carbon—and varying operational times on the reduction of pH, COD, TSS, and phosphate levels in laundry wastewater. A PVC-based gravity-flow (down-flow) filtration reactor was operated using three media composition variations: activated carbon-dominant (P1), bagasse-dominant (P2), and silica sand-dominant (P3), with operational times of 30, 60, and 90 minutes. The results indicated that variation P1 achieved the highest COD reduction efficiency (36.98%), while variation P3 yielded the greatest TSS reduction (98.18%). The pH levels of all effluents met the quality standards established by East Java Governor Regulation No. 52 of 2014. However, COD levels failed to meet the threshold across all treatments, and phosphate levels increased due to leaching from the bagasse media. Multiple linear regression analysis revealed that filtration media thickness significantly influenced effluent pH and TSS, whereas operational time did not have a significant partial effect on any of the parameters. As this filtration system could not simultaneously meet all quality standards, further treatment is required to enhance its effectiveness.